1985
DOI: 10.1902/jop.1985.56.10.618
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Bacteria within the Oral Epithelium in Periodontal Disease: I. A Scanning and Transmission Electron Microscopic Study

Abstract: The presence of bacteria within the gingival oral epithelium and adjacent connective tissue in cases of periodontitis and localized juvenile periodontitis have been described using scanning and transmission electron microscopy. The following bacterial morphotypes were identified: cocci, short rods, filaments and few spirochetes in periodontitis and mainly coccobacillary-shaped bacteria in localized juvenile periodontitis. Also Mycoplasma-like structures were identified in the localized juvenile periodontitis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…Saglie et al, (1985) have suggested that initial points of entry for bacteria are the undersides of desquamating epithelial cells and along their intercellular spaces. Saglie et al, (1985) have suggested that initial points of entry for bacteria are the undersides of desquamating epithelial cells and along their intercellular spaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Saglie et al, (1985) have suggested that initial points of entry for bacteria are the undersides of desquamating epithelial cells and along their intercellular spaces. Saglie et al, (1985) have suggested that initial points of entry for bacteria are the undersides of desquamating epithelial cells and along their intercellular spaces.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Allen & Brady (1978), Gillett & Johnson (1982), Saglie et al (1982), Carranza et al (1983), Newman et al (1984) ail obtained 4 or less specimens from one patient. In addition, Saglie et al (1985), Saglie et al (1986) and Liakoni et al (1987) based their studies on a sample population of 2 patients. One major study by Gonzalez et al (1987) used a patient population of twelve from which sixty specimens were procured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study was in Japanese and was excluded. 36 Twenty-two studies were subsequently excluded for specific reasons: 3 studies 34,35,37 had a study protocol not related to the objectives of this systematic review, 8 studies 14,[25][26][27]30,39,40,42 had absence of control group (non-diseased samples), one study 38 only presented disease samples from a single patient, 7 studies 28,29,[31][32][33]41,44 hadn't clearly defined inclusion and/or exclusion criteria, and finally 3 studies 43,45,46 were excluded because they only addressed opportunistic pathogens. Additional hand searching of the reference lists of the selected papers didn't retrieve any additional studies.…”
Section: Search and Selection Resultsmentioning
confidence: 99%